(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article discusses the improvement of wrestling technical skills, participation of wrestlers in competitions, mastering of wrestling methods, technical-tactical and preparation. Also, during the competitions, the use of wrestling methods, the physical and mental preparation of wrestlers, the application of anti-aging methods to the opponent’s actions, the most and perfectly performed methods, and the physiological capabilities of wrestlers were scientifically researched.